High‐frequency modelling of permanent magnet synchronous motor with star connection. Issue 4 (13th February 2018) - Wu, Yingzhe; Bi, Chuang; Jia, Kelin; Jin, Dingxin; Li, Hui; Yao, Weizheng; Liu, Gang
Abstract : Permanent magnet synchronous motor (PMSM) has been widely applied in a pulse width modulation inverter‐fed adjustable speed drive (ASD) system. However, electromagnetic interference (EMI) has become a critical issue in such a system. Plenty of high‐frequency harmonic components, generated by high d v /d t or d i /d t of the modern transistors, can be observed on the line‐to‐line voltage across motor terminals. To study the conducted EMI issues existed in the ASD system, an improved model of PMSM is developed to represent the high‐frequency behaviour, and the equivalent circuit parameters for common mode (CM) and differential mode (DM) are extracted based on the measurements. The model calculated CM and DM impedances are in good agreement with the measured ones from the impedance analyser, which verifies the effectiveness of the proposed high‐frequency model.